Can you afford to be ill : hospital service plan (London : The London Association for Hospital Services Limited)
1945 1945 1940s 15 pages : illustrations How the Hospital Service Plan benefits you Sectional rates of repayment for maintenance and medical services are given below. They apply only to In-Patient treatment. The maximum amount repayable to a registered subscriber (and or dependants) is £105 covering a maximum aggregate period of six weeks in any one membership year. Hospital or Nursing Home Charges. Rate £ s. d. In-Patient maintenance, including the use of operating theatre, etc. weekly up to 6 0 0 (Subject to an aggregate maximum of six weeks in any membership year) Fees of Physicians and Surgeons. *SURGICAL CASES. Major surgical operation .. .. up to 26 5 0 Intermediate surgical operation .. .. .. 13 13 0 Minor surgical operation .. .. .. 5 5 o MEDICAL CASES. Period of two days .. .. up to 2 12 6 Period of three days .. .. .. 3 3 o Period up to one week .. .. .. 3 5 o Daily rate after the first week .. .. .. 15 o (Subject to an aggregate maximum of £52 10s. in any membership year) Anaesthetist Services. Major or Intermediate operation .. .. .. 3 3 0 Minor operation .. .. .. 1 1 0 (Subject to an aggregate maximum of £5 5s. in any membership year) *NOTE : A schedule of the classification of operations can be seen on application to the Secretary. Consultations during an In-Patient treatment period. (Not included above) .. .. up to 2 2 0 (Subject to an aggregate maximum of £6 6s. in any membership year) Radiodiagnostic Service. .. .. up to 3 3 0 (Subject to an aggregate maximum of £6 6s. in any membership year) 7 292/842/2/63